If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11X + 12 = 4X + 24 Reorder the terms: 12 + 11X = 4X + 24 Reorder the terms: 12 + 11X = 24 + 4X Solving 12 + 11X = 24 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 12 + 11X + -4X = 24 + 4X + -4X Combine like terms: 11X + -4X = 7X 12 + 7X = 24 + 4X + -4X Combine like terms: 4X + -4X = 0 12 + 7X = 24 + 0 12 + 7X = 24 Add '-12' to each side of the equation. 12 + -12 + 7X = 24 + -12 Combine like terms: 12 + -12 = 0 0 + 7X = 24 + -12 7X = 24 + -12 Combine like terms: 24 + -12 = 12 7X = 12 Divide each side by '7'. X = 1.714285714 Simplifying X = 1.714285714
| 2(12x+11)=12(2x+12) | | 2(3x-5)+2x= | | 3/5x/74/5 | | -9r=-9 | | 5x+20+4x+11=180 | | 5x^2+46x+9=0 | | 180+4x=180 | | 24+5x=3+5(x+5) | | x+12=2(x+6)+4 | | x=-8y-7 | | -10+3b=5b-26 | | 5x+11=2x+46 | | 9a-7a+7-4= | | x^3+4*x=54 | | 13+3m=3m+13 | | F(2.5)=2x^2+3x-7 | | 6(v+3)=9v+39 | | 8*4+n=112 | | xcubed+4x=54 | | 8x=41-1(1-3x) | | 259+38+17= | | 6x-x+5-2= | | -4(9x-5)=-12+4x | | (2n+5)(-3)=-57 | | (180-20)/2 | | 11-175=5-13 | | 368/8= | | -4(7x+2)=-92 | | 8q^2x3q^7/6q^8 | | 9+-y=-26+7y | | 7(2+3x)-5=114 | | (2x+1)*(3x^2+2x+1)=0 |